Change in Serum Lactate Dehydrogenase Is Associated with Outcome of Patients with Advanced-stage NSCLC Treated with Erlotinib - Fiala, Ondrej; Pesek, Milos; Finek, Jindrich; Topolcan, Ondrej; Racek, Jaroslav; Svaton, Martin; Kucera, Radek; Minarik, Marek; Benesova, Lucie; Bortlicek, Zbynek; Chloupkova, Renata; Poprach, Alexandr; et al. (Anticancer research, 2016)
BACKGROUND: Serum lactate dehydrogenase (LDH) has been reported as a prognostic biomarker in malignant diseases. However, little is known on the dynamics of serum LDH levels during systemic treatment. We focused on the association of changes in serum LDH with outcome of patients with advanced-stage non-small cell lung cancer (NSCLC) treated with erlotinib. PATIENTS AND METHODS: Clinical data of 309 patients were analyzed. Serum samples were collected within one week before initiation and after one month of treatment. RESULTS: The change in serum LDH during the first month of erlotinib treatment was independently associated with disease control rate (p=0.006), progression-free survival (PFS) (p=0.010) and overall survival (OS) (p<0.001). CONCLUSION: LDH is a commonly used serum biomarker, that is cheap and easy to detect. The results of our study suggest that the change in LDH serum level during the first month is a surrogate marker on the efficacy of erlotinib in patients with advanced NSCLC.
Keywords: senioři; senioři nad 80 let; NSCLC; Retrospective Studies; výsledek terapie; Middle Aged; mužské pohlaví; nádory plic; L-laktátdehydrogenasa; Adult; Antineoplastic Agents; Lactate dehydrogenase; Aged, 80 and over; biomarker; nemalobuněčný karcinom plic; ženské pohlaví; protinádorové látky; retrospektivní studie; Humans; lung cancer; L-Lactate Dehydrogenase; erlotinib; EGFR-TKI; Carcinoma, Non-Small-Cell Lung; lidé středního věku; Erlotinib Hydrochloride; LDH; dospělí; prediction; Female; Aged; Treatment Outcome; Lung Neoplasms; lidé; Male